SNOW-COMPACTION EQUIPMENT - MODEL 36/42 SNOW MIXER. - Sherwood, G. E.; Hansen, R. W. (1966)
Commercially available towed-type construction mixers were modified as snow mixers for depth-processing to produce high-strength snow. The mixers, designated as model 36/42 snow mixers, each employ a high-speed rotor to thoroughly pulverize and intermix the natural snow. Interchangeable 36-inch-diameter and 42-inch-diameter rotors 8 feet long are used. Three-pass offset processing with the model 36/42 mixer was found to be as effective as double depth- processing requiring six mixer passes with the models 24 and 42 snow mixers. A two-pass tailgate processing technique, developed with the model 36/42 mixer during Deep Freeze 66, was found to produce a snow pavement equivalent to that of three-pass offset processing under similar conditions. It was concluded that the model 36/42 snow mixer is effective in depth-processing natural snow to produce high strengths. Well-trained operators and good overlap techniques are essential for obtaining a compacted- snow area of uniform strength. To improve the strength in processed snow and to reduce the manpower and equipment required for processing, a single-pass, double-rotor snow paver should be developed to replace the model 36/42 snow mixer. (Author)